2020
DOI: 10.1155/2020/4969486
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumomediastinum Associated with COVID-19 Pneumonia

Abstract: The first case of coronavirus disease 2019 (COVID-19) was declared in December in Wuhan, before becoming a global pandemic in a few weeks. Several complications of this infection have been reported. However, a spontaneous pneumomediastinum has rarely been described. We report the fourth case of this extremely rare complication in a 65-year-old male patient with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pneumonia, discovered during his therapeutic management by a CT scan control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…The exact mechanism of SP in non-ventilated patients remains unknown. However, the Macklin effect has been proposed as a possible etiology [3] owing to the SARS-CoV-2 propensity to damage type 2 pneumocytes [4]. The Macklin effect starts with alveolar rupture secondary to direct alveolar injury, leading to air leaking and dissection along the bronchovascular sheaths and eventually spreading of air within the mediastinum [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanism of SP in non-ventilated patients remains unknown. However, the Macklin effect has been proposed as a possible etiology [3] owing to the SARS-CoV-2 propensity to damage type 2 pneumocytes [4]. The Macklin effect starts with alveolar rupture secondary to direct alveolar injury, leading to air leaking and dissection along the bronchovascular sheaths and eventually spreading of air within the mediastinum [5].…”
Section: Discussionmentioning
confidence: 99%
“…The air-leak can also spread to the fascial planes of the neck and chest leading to subcutaneous emphysema, which was also a manifestation in our patient. The most common symptom of pneumomediastinum is acute retrosternal chest pain [4] and should warrant early alert to rule out this dreaded complication in patients with suspected or confirmed COVID-19. However, our patient did not complain of retrosternal chest pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen therapy has been described to increase the resorption of free air in the mediastinum secondary to a higher nitrogen concentration. Continued treatment for COVID-19 is also essential as the virus may continue to damage type II pneumocytes in the lungs and subsequently damage alveolar membranes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, COVID-19 infection is confronted with this complication, which can further deteriorate the patient. The current literature search yields scarce case reports of this complication and one research by Eperjesiova et al reported a 0.72% incidence of spontaneous air leak in COVID-19 cases (Table1)[2][3][4][5][6][7].…”
mentioning
confidence: 99%